Program Bimbingan Belajar Bahasa Asing bagi Siswa Sekolah Dasar Selama Masa Libur Sekolah di Desa Larangan Dalam Kecamatan Larangan Kabupaten Pamekasan - Rahmawati, Fithriyah; Komariyah, Elita Isti; Ardiansyah, Ferdi (Dharma: Jurnal Pengabdian Masyarakat, 2023)
This community service was about a foreign learning course for elementary students in the Larangan Dalam Village during the semester break. By conducting this program, the students had an interesting activity that enable them to improve their skills in Arabic and English languages. The current program was one of the agendas of the facilitators of the Community Service Lecture (KPM) of the Tarbiyah Faculty IAIN Madura in 2022. The community service was attended by approximately 20 students in every meeting. The result of the community service was about their interest in learning and their achievement after the course. During the course, the students were learning Arabic and English language calmly, comfortably, and enthusiastically. The program also gained positive responses from the students, parents, and community of Larangan Dalam.